Fatal hepatotoxicity due to sevoflurane use in a paediatric patient after aortic repair: reality or fiction? A case of pharmacovigilance. Issue 1 (8th April 2021) - Sanchez, Llefer V.; Pichardo, Pol; Adames, Vicky; Zovi, Andrea; Pradegan, Nicola
Abstract : Hepatotoxicity secondary to exposure of volatile anaesthetics is an exceptional finding, but its clinical interest depends on their frequent use, unpredictable appearance and potential severity. Halothane is the volatile anaesthetic most frequently involved in the development of liver dysfunction, especially after re-exposure. Sevoflurane has rarely been related to this life-threatening complication. We present the case of a 1-year-old girl who had undergone previous surgery for closure of a patent ductus arteriosus, and who developed severe acute hepatitis and died after undergoing surgical repair of an aortic isthmus narrowing by means of general anaesthesia with sevoflurane. Other possible causes of liver failure were excluded. This adverse event was classified as serious and was included in the national and European pharmacovigilance network, with the aim of preventing dangerous effects on patient health in clinical practice, by contributing to the enrichment of the literature.